Sexual Safety for In-Patient Mental Health Care—The Democratic Diagnosis of Change. (2nd September 2019) - Page, Sean; Carr, Tony; Forsyth, Steve; O'Hara, Amber; Burgess, Jenny; Charles, Denise
Abstract: This article discusses a co-produced qualitative understanding aimed at reducing the risk of sexual violence within mental health in-patient settings. It describes the first stages of testing a new approach which democratises organisational change as, people who use mental health services take the lead in partnership working with those who provide services. The article sets out 'TODAYICAN' (and its second-generation iteration, 'TODAYWECAN') as emerging approaches towards change. In particular, the article focusses upon the 'diagnose' component of the approach and reports findings from a mixed methods qualitative methodology. In doing so the article offers a conceptualisation of in-patient sexual safety in a mental health context drawn from the perspectives of people who use or provide in-patient services. The article also outlines where the consensus rests on what needs to change to make sexual safety an 'always event' whilst, critically analysing where the two groups differed in their views.